MORAL EDUCATION FROM THE PERSPECTIVE OF BUYA HAMKA AND IBNU MISKAWAIH IN THE MODERN CONTEXT - Ahmad Faidzal; Nurjanah Nurjanah (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
This research aims to explore understanding of moral education from the perspective of two main figures, namely Buya Hamka and Ibnu Miskawaih. This research uses qualitative methods with the type of research used is library research. Both are considered classical figures who made significant contributions to Islamic thought, especially related to moral education. This research includes an analysis of Buya Hamka's written works, especially those related to moral education, and Ibnu Miskawaih's works such as